CRUSTAL MOVEMENTS ALONG THE NW HELLENIC VOLCANIC ARC FROM DGPS MEASUREMENTS - Papageorgiou, E. (Bulletin of the Geological Society of Greece, 2010)
The north-western part of the Hellenic Volcanic Arc was studied by Differential GPS measurements in an attempt to investigate the regional deformation of the area. The GPS network involving stations in Athens, Aegina Island, Methana Peninsula and Soussaki was established in February 2006 and since then it was reoccupied twice. The GPS measurements were primarily referred to Worldfixed reference frame (ITRF2000) and then to Europe and Athens as well. The observed velocities for the overall three-year spanning period according to Athens station showed rates at the order of 7-10 mm/yr, while the directions of the displacements tend towards NNW to NNE. The results of the horizontal velocities with respect to Europe indicate rates of SW directions, exhibiting higher magnitudes (25-26±2mm/yr) in the western and southern part of the Saronikos Gulf than in its central part (20±7 mm/yr). The horizontal velocities with respect to ITRF2000 showed consistent SE directions with higher rates in Aegina (12±7 mm/yr) than in Soussaki and Methana (9±3 mm/yr). A kinematic interpretation based on velocity and strain rates is finally attempted on the basis of the regional tectonics in the Saronikos Gulf.